2016
DOI: 10.1111/mcn.12304
|View full text |Cite
|
Sign up to set email alerts
|

Promotion and consumption of commercially produced foods among children: situation analysis in an urban setting in Senegal

Abstract: This study assessed the promotion of commercially produced foods and consumption of these products by children less than 24 months of age in Dakar Department, Senegal. Interviews with 293 mothers of children attending child health clinics assessed maternal exposure to promotion and maternal recall of foods consumed by the child on the preceding day. Promotion of breastmilk substitutes and commercially produced complementary foods outside health facilities was common with 41.0% and 37.2% of mothers, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
(17 reference statements)
6
37
0
1
Order By: Relevance
“…Although not explicitly a Code violation, a large number of health providers in Mexico (30.5%) recommend infant formulas, far more than would be expected for the small number of women who for medical reasons should use infant formula. Similar results were reported in Cambodia (Pries et al, ) and Senegal (Feeley et al, ). As recognized in the Coriolis report Infant Formula Value Chain (Coriolis, ), the major global multinationals direct a large part of their sales effort towards health providers rather than retailers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although not explicitly a Code violation, a large number of health providers in Mexico (30.5%) recommend infant formulas, far more than would be expected for the small number of women who for medical reasons should use infant formula. Similar results were reported in Cambodia (Pries et al, ) and Senegal (Feeley et al, ). As recognized in the Coriolis report Infant Formula Value Chain (Coriolis, ), the major global multinationals direct a large part of their sales effort towards health providers rather than retailers.…”
Section: Discussionsupporting
confidence: 87%
“…Among the reported violations are those related to pregnant women and mothers of children aged between 6 and 24 months receiving free BMS samples (Access to Nutrition Foundation, ; Aguayo et al, ; Changing Markets Foundation, ; Ching & IBFAN‐ICDC, ; Taylor, ), in addition to health facilities receiving donations of BMS that were not used for research or professional purposes and having educational materials with BMS producer logos (Aguayo et al, ; Pries et al, ). Other studies have identified that promotion of BMS outside of health facilities is a common practice in Cambodia (Pries et al, ) and Senegal (Feeley et al, ), as is promotion within health facilities (Coriolis, ; Pries et al, ). BMS promotion at POS has been identified in Senegal, Cambodia, Nepal, and Tanzania (Champeny et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of child preference on caregivers' use of snack food products for child feeding has been noted widely in literature across geographies (Almeida, Scagliusi, Duran, & Jaime, ; Angeles‐Agdeppa, Lana, & Barba, ; Babington & Patel, ; Feeley et al, ; Machín, Giménez, Curutchet, Martínez, and Ares (); Kavle et al, ; Pries, Huffman, Adhikary, et al, ; Pries, Huffman, Mengkheang, et al, ; Rahman et al, ; Verma & Punia, ; Vitta et al, ). Child preference was the most common reason reported by caregivers in this study; however, this response may serve as an initial catch‐all response.…”
Section: Discussionmentioning
confidence: 99%
“…The very low rates of maternal exposure to promotions of breastmilk substitutes and commercially produced complementary foods and the low rates of use of these products are likely related to Tanzania's strict regulations limiting their promotion [ Tanzania Food, Drugs and Cosmetics (Marketing of foods and designated products for infants and young children) Regulations, 2013; Government of Tanzania ]. In Senegal, where the promotion of breastmilk substitutes is allowed outside of the health system, breastmilk substitute use is more prevalent: about 10% of infants less than 6 months of age and 20% of 6–23‐month‐olds in Dakar received a breastmilk substitute on the day preceding the interview compared with 4% and 5%, respectively, in Dar es Salaam (Feeley et al In press).…”
Section: Discussionmentioning
confidence: 99%